Geographical analysis of primary education services in yathrib district - Ali Faiq Mishal Qaddouri AlObaid; Aziz Ibrahim Ali Obaid AlAzzawi (Genius Journals, 2025)
The educational position is a human development process for the trained forces that require economic development plans for the society, and that educational services and the population dire need for them as the lifeblood of contemporary urban life and the source of its growth and development in a way that the residents of the district cannot do without. the study clarified the population distribution, and the gender and age structure of the population, the study showed the concentration occurring in a small area from one side to the other, as for what was shown by the presumption of the nearest neighbor to primary schools, it is similar to the value the nearest neighbor index has a value of(1.08) which indicates the existence of a randomly distributed pattern, this spatial distribution is the result of such randomness an irregularity in some villages and their lack of presence in other neighborhoods, the study also showed that the population increase witnessed by the sub- district constitutes a great pressure on the volume of educational services in it, which generates a shortage in the volume of educational services, the study confirmed the efficiency of educational services based on local criteria such as the degree of satisfaction and accessibility
Keywords: Educational services; Functionality; Degree of satisfaction